Gangguan Berbahasa pada Anak Korea Usia 5 Tahun: Kajian Psikolinguistik - Velayeti Nurfitriana Ansas; Shafia Fartsa Hadiwijaya (Universitas Pendidikan Indonesia, 2023)
This study discusses the language disorders found in the video요즘 육아 금쪽같은 내새끼 (yeojeum yuka geumjjokgateun naesekki) ‘These days, my child who is like a golden child’ episode 59 in 2021 on youtube channel 채널에이방송영상 (chaenoleibangsongyongsang). The purpose of this study is to find out what language disorders exist in the subject and how to deal with them. This study uses descriptive qualitative methods to describe language disorders that occur in the subject. The data collection technique used is the simak catat technique. Technique simak catat conducted by researchers to obtain data from videos, then data related to language disorders, especially autism will be recorded for further research. The results show that in fact the speech delay experienced by Jian is part of the impact of the autism aspect on Jian. Then, detecting early age development is very important, because it can help mothers or families to find out if there are obstacles in early age development and prevent delays in handling or misdiagnosis.